O uso da realidade aumentada no ensino dos poliedros de Platão e relação de Euler na 2° série do ensino médio na Escola Estadual Professora Mirtes Rosa de Mendes de Mendonça Lima no município de Itacoatiara - AM - Silva, Anderson Deodato da (Brasil, 2022)
Teaching and learning in classrooms goes through moments of transformation that occur due to new technologies, which, little by little, are inserted and interconnected with educational activities. Among these technologies, Augmented Reality (AR) has been growing in the educational environment, for superposing environments and virtual objects on a real environment. This technology was used in our work as a didactic strategy to teach 2nd year students at the State School Professor Mirtes Rosa de Mendes de Mendonça Lima (Itacoatiara – AM), the contents of Spatial Geometry, Plato's Polyhedra and Euler's Relation. The students used AR technology on mobile devices, from the Geometrix software, which sought to emphasize the three-dimensional visualization, and elements and characteristics of Plato's solids. The methods used during the field work, and for data collection for this research were: the application of questionnaires and participant observation. The results were satisfactory in relation to the use of AR technology, it was evident from the students' answers how important and useful it is to make use of this type of tool in the classroom.